Effectiveness of mRNA COVID-19 vaccines against Omicron and Delta variants in a matched test-negative case–control study among US veterans - Maria C Rodriguez-Barradas; Vincent C Marconi; Yinong Young-Xu; Gabrielle M Zwain; Hector S Izurieta; Caroline Korves; Ethan I Powell; Jeremy Smith; Abirami Balajee; Mark Holodniy; David O Beenhouwer; Sheldon T Brown (BMJ Open, 2022)
Objective To estimate the effectiveness of messenger RNA (mRNA) booster doses during the period of Delta and Omicron variant dominance.Design We conducted a matched test-negative case–control study to estimate the vaccine effectiveness (VE) of three and two doses of mRNA vaccines against infection (regardless of symptoms) and against COVID-19-related hospitalisation and death.Setting Veterans Health Administration.Participants We used electronic health record data from 114 640 veterans who had a SARS-CoV-2 test during November 2021–January 2022. Patients were largely 65 years or older (52%), male (88%) and non-Hispanic white (59%).Main outcome measures First positive result for a SARS-CoV-2 PCR or antigen test.Results Against infection, booster doses had higher estimated VE (64%, 95% CI 63 to 65) than two-dose vaccination (12%, 95% CI 10 to 15) during the Omicron period. For the Delta period, the VE against infection was 90% (95% CI 88 to 92) among boosted vaccinees, higher than the VE among two-dose vaccinees (54%, 95% CI 50 to 57). Against hospitalisation, booster dose VE was 89% (95% CI 88 to 91) during Omicron and 94% (95% CI 90 to 96) during Delta; two-dose VE was 63% (95% CI 58 to 67) during Omicron and 75% (95% CI 69 to 80) during Delta. Against death, the VE with a booster dose was 94% (95% CI 90 to 96) during Omicron and 96% (95% CI 87 to 99) during Delta.Conclusions Among an older, mostly male, population with comorbidities, we found that an mRNA vaccine booster was highly effective against infection, hospitalisation and death. Although the effectiveness of booster vaccination against infection was moderately higher against Delta than against the Omicron SARS-CoV-2 variant, effectiveness against severe disease and death was similarly high against both variants.